3D Printing of Dapagliflozin Containing Self-Nanoemulsifying Tablets: Formulation Design and In Vitro Characterization - Mohammed S. Algahtani; Abdul Aleem Mohammed; Javed Ahmad; M. M. Abdullah; Ehab Saleh (MDPI AG, 2021)
The 3D printing techniques have been explored extensively in recent years for pharmaceutical manufacturing and drug delivery applications. The current investigation aims to explore 3D printing for the design and development of a nanomedicine-based oral solid dosage form of a poorly water-soluble drug. A self-nanoemulsifying tablet formulation of dapagliflozin propanediol monohydrate was developed utilizing the semisolid pressure-assisted microsyringe (PAM) extrusion-based 3D printing technique. The developed formulation system consists of two major components (liquid and solid phase), which include oils (caproyl 90, octanoic acid) and co-surfactant (PEG 400) as liquid phase while surfactant (poloxamer 188) and solid matrix (PEG 6000) as solid-phase excipients that ultimately self-nanoemulsify as a drug encapsulated nanoemulsion system on contact with aqueous phase/gastrointestinal fluid. The droplet size distribution of the generated nanoemulsion from a self-nanoemulsifying 3D printed tablet was observed to be 104.7 ± 3.36 nm with polydispersity index 0.063 ± 0.024. The FT-IR analysis of the printed tablet revealed that no drug-excipients interactions were observed. The DSC and X-RD analysis of the printed tablet revealed that the loaded drug is molecularly dispersed in the crystal lattice of the tablet solid matrix and remains solubilized in the liquid phase of the printed tablet. SEM image of the drug-loaded self-nanoemulsifying tablets revealed that dapagliflozin propanediol monohydrate was completely encapsulated in the solid matrix of the printed tablet, which was further confirmed by SEM-EDS analysis. The in vitro dissolution profile of dapagliflozin-loaded self-nanoemulsifying tablet revealed an immediate-release drug profile for all three sizes (8 mm, 10 mm, and 12 mm) tablets, exhibiting >75.0% drug release within 20 min. Thus, this study has emphasized the capability of the PAM-based 3D printing technique to print a self-nanoemulsifying tablet dosage form with an immediate-release drug profile for poorly water-soluble drug.